A method to produce periodic varied structural composite yarn by forced migrations of convergence point between polymer filaments and the staple strand - Chen, Ze; Li, Wei; Peng, Zhiyong; Zhang, Ruicheng; Wang, Xin; Xu, Weilin; Xu, Duo; Liu, Keshuai (Frontiers in Materials, 2023)
A novel composite yarn with a novel structure is prepared by the three-strand conversion method of double polymer filaments to staple fiber, that is, double polymer filaments to staple fiber repeated migration movement. The geometric principle of different relative positions of filament to helix structure change is analyzed theoretically, and the effect of filament position on the spinning-triangle of composite yarn is demonstrated. Furthermore, the structure of six different composite yarns is modeled and compared with each other, which shows the influence of different filament helical structures on the performance of spinning composite yarns. The repeated migration of filaments is observed using the online observation technique in the dynamic rotating triangle region. In addition, changes in yarn structure are caused by different geometric configurations. The results show that the stem, strength, and hair of six new composite yarns with different helical structures are slightly weakened. In summary, the three-strand conversion method is an effective new method to control the structure of filament and staple fibers.